Optical characterization of organic light-emitting diodes with selective red emission. (2021) - Gioti, M.; Tselekidou, D.; Panagiotidis, L.; Kyriazopoulos, V.; Simitzi, K.; Andreopoulou, A.K.; Kalitsis, J.K.; Gravalidis, C.; Logothetidis, S.
Abstract: In this work, the optical properties of red-light emitting materials used for active layers in functional red OLED devices were researched. The investigated materials are: a synthesized lab scale complex vinyl-quinoline pyridine homopolymer with Ir P[QPy-Ir-(PPy)2 ], as well as two commercially supplied materials, Poly[2-methoxy-5-(3′, 7′-dimethyloctyloxy)-1, 4-phenylenevinylene] (MDMO-PPV) and Poly[2-methoxy-5-(2-ethylhexyloxy)-1, 4-phenylenevinylene] (MEH-PPV). The samples were spin-coated on ITO/glass substrates. The characterization of the materials was carried out via Spectroscopic Ellipsometry (SE), Photoluminescence Spectroscopy (PL) and Electroluminescence Spectroscopy (EL). Through SE analysis the film thickness, the optical properties and the dielectric function were obtained. PL and EL spectra were derived and evaluated in terms of the emission profile and characteristics of the different photoactive materials. Finally, the colour stability and selectivity of each material were determined, and a comparative study of the red-light emitting materials was conducted.